Design and Fabrication of an Intelligent Walking Staff for Visually Impaired Subjects - Rashidah Funke Olanrewaju; Muhammad Luqman Azzaki Mohd Radzi; Mariam Rehab; Fawwaz Eniola Fajingbesi (Institute of Advanced Engineering and Science, 2018)
The joy we derive from our ability to commute and interact freely with the world as a result of our possession of sight with the naked eyes are enormous however the Visually impaired people find great difficulty in moving around freely without a human guide, especially in a new terrain. This research reports the design and fabrication process of an intelligent walking staff (iWalk) specially designed for the visually disabled individuals to argument their loss of sight, improve and ease their navigation. iWalk was designed around water and ultrasonic sensors to detect obstacles and water ahead. iWalk also has a wireless RF remote control buzzer for localization and detection in case it gets misplaced. The proposed system operability and efficiency was adequately tested using physical dataset composed of randomized locations with random obstacles and water. The proposed algorithm achieves an overall efficiency of 90% detection rate for water and ultrasonic sensor and 85.75% for the RF wireless remote control.